Hysteretic Behavior Study on the RBS Connection of H-Shape Columns with Middle-Flanges or Wide-Flange H-Shape Beams - Saleem Mohammed Ali Ahmed Al-Saeedi; Linfeng Lu; Osama Zaid Yahya Al-Ansi; Saddam Ali (Buildings)
Existing research on reduced beam section (RBS) connections in steel frames rarely addresses H-shaped beams with middle and wide flanges. Therefore, this study investigates the hysteretic behavior of RBS connections in H-shaped columns connected to H-shaped beams with middle and wide flanges. Using finite element analysis, the influence of key parameters (a, b, and c, where “a” represents the unweakened beam flange extension length, “b” represents the weakened beam flange length, and “c” represents the weakened beam flange depth, respectively) on structural performance was evaluated, focusing on rotational stiffness, load-carrying capacity, plastic rotation capacity, and ductility. The results indicate that increasing a enhances initial rotational stiffness and load capacity but reduces plastic rotation and ductility, making lower a values (near 0.5bf) optimal for ductile performance. Similarly, higher b values (up to 0.85bf) marginally reduce stiffness and load capacity, improving plastic rotation capacity, with a greater benefit in wide-flange beams. Meanwhile, a lower c value (around 0.20bf) offered balanced performance, with higher c values decreasing stiffness and load capacity but enhancing ductility. Overall, wider flanges improve plastic rotation and ductility but slightly decrease rotational stiffness, providing insights to guide RBS connection designs for seismic resilience.